Efektivitas Program Keluarga Harapan (PKH) Dalam Meningkatkan Kesejahteraan Masyarakat - Baiq Dewi Kamariani; Nur Fitri Eka Asbarini; Asrifia Ridwan; Abdul Chalel Rahman (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
This research is entitled "The effectiveness of the Family Hope Program (PKH) in improving community welfare. The aim of this research is to determine the level of effectiveness of the family hope program in improving community welfare in Suryawangi Village. This research is a qualitative descriptive study with the research location in Suryawangi Village. Data collection techniques include primary data collection (observation and interviews). Data analysis in this research includes three components consisting of data reduction, data presentation, and drawing conclusions/data verification. The results of this research show that the effectiveness of the family hope program in improving community welfare in Suryawangi Subdistrict has been declared good and can help reduce the burden of community expenditure. The indicators of effectiveness are understanding the program, being on time, right on target, achieving goals and real changes that have gone well. However, this PKH cannot be said to be completely effective in terms of improving community welfare if seen from the indicators of target accuracy and punctuality.